(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to determine the prevalence of dental erosion among 10- 12 year old children in Mosul city, mean erosion in teeth and surfaces, amount of carbonated beverages and fruit juice consumed in the sample, and the correlation between dental erosion and some variables. Total sample consisted of 400 children derived from different primary schools in the city center. Examination was performed according to tooth wear index by Smith and Knight 1984 modified by Millword et al 1994. Results showed that dental erosion was highly prevalent 74.2% in the sample, increasing with increasing age, with boys showing a higher prevalence in dental erosion compared to girls with significant difference. Mean erosion scores for primary teeth were slightly less then permanent teeth, with a significant difference between 10 and 12 years of age for both dentitions. Buccal/labial surfaces exhibited more erosion, followed by lingual/palatal and finally occlusal /incisal surfaces, with boys showing more erosion in all surfaces than girls. A large proportion of the sample consumed carbonated beverages 3-5 /week with boys consuming more than girls as seen in the erosion group, fruit juice was also largely consumed by the sample, especially the group that showed erosion. A positive correlation was found between erosion, level of father’s education, time of drinking, method, amount of carbonated beverages and fruit juice consumed. Preventive measures are considered to be the only effective course of management of dental erosion, by reducing intake of carbonated beverages and fruit juice, also modification of erosive drinks, medicines and foods may prove to be an acceptable future strategy world wide.